2018
DOI: 10.1016/j.ctarc.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime physical inactivity is associated with lung cancer risk and mortality

Abstract: These data add to the body of evidence suggesting that physical inactivity is an independent risk and prognostic factor for cancer. Additional research utilizing prospectively collected data is needed to substantiate the current findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Among never-smokers (OR = 3.00, 95% CI: 1.33–6.78) and former smokers (OR = 3.00, 95% CI: 1.33–6.78) the association was significant as well. The authors also described a significant positive correlation between lifetime physical inactivity and the mortality from lung cancer [Hazard ratio (HR) = 1.40, 95% CI: 1.14–1.71]; here the association remained significant also for the non-smoking patients [42]. A different study published in 2017 also evaluated the impact of physical activity on lung cancer risk.…”
Section: Physical Inactivitymentioning
confidence: 97%
See 2 more Smart Citations
“…Among never-smokers (OR = 3.00, 95% CI: 1.33–6.78) and former smokers (OR = 3.00, 95% CI: 1.33–6.78) the association was significant as well. The authors also described a significant positive correlation between lifetime physical inactivity and the mortality from lung cancer [Hazard ratio (HR) = 1.40, 95% CI: 1.14–1.71]; here the association remained significant also for the non-smoking patients [42]. A different study published in 2017 also evaluated the impact of physical activity on lung cancer risk.…”
Section: Physical Inactivitymentioning
confidence: 97%
“…Cannioto et al investigated the association of physical inactivity with lung cancer [42]. Since it has been proven for many types of malignant disease that lifetime inactivity goes along with an increased cancer risk, the authors wanted to show whether this holds true also for lung cancer, independently of other risk factors such as smoking.…”
Section: Physical Inactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors affect individuals’ physical and mental health. It has been shown that physical inactivity may play an important mediating role in some physical and psychological disorders [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in subgroup analyses by BMI classification we observed a statistically significant association between physical inactivity and increased mortality among overweight/obese patients that did not persist in normal weight patients. Because physical inactivity has been shown to associate with cancer endpoints independently of obesity, 32 these observations suggest that physical activity may confer an additional survival benefit in the overweight/obese population.…”
Section: Discussionmentioning
confidence: 99%